EMBR-10. GENOMIC COMPLEXITY AND EVOLUTION OF EMBRYONAL TUMORS WITH MULTILAYERED ROSETTES (ETMR). Issue 2 (22nd June 2018) - Lambo, Sander; Waszak, Sebastian M; Rausch, Tobias; Groebner, Susanne; Schmidt, Christin; Brabetz, Sebastian; Pfister, Stefan M; Korshunov, Andrey; Kool, Marcel
Abstract: Embryonal Tumors with Multilayered Rosettes (ETMRs) are aggressive pediatric brain tumors mainly occurring in infants. In order to develop alternative treatment strategies for this deadly disease there is an urgent need for better understanding the mechanisms driving these tumors. We therefore analyzed a cohort of 60 ETMRs using whole genome and panel sequencing, DNA methylation, mRNA expression profiling, and miRNA sequencing. The genetic hallmark of ETMRs is amplification of miRNA cluster C19MC fused to TTYH1 present in ~90% of all ETMRs. ETMRs lacking the C19MC amplification are biologically highly similar to tumors with C19MC amplification, indicating that they do not represent a distinct subgroup. DNA sequencing revealed germline mutations affecting DNA repair genes or miRNA processing genes in a subset of cases, while tumor specific mutations included genes involved in the TP53-, SHH- WNT-, or miRNA processing pathways. Prevalence of mutations in miRNA processing pathways are specifically high in tumors without C19MC amplification, however overall recurrence of mutations is low within our cohort. We also detect high recurrence of genomic instability shown by pluriploidy, large abundance of CNVs, highly upregulated DNA repair pathways and chromothripsis primarily centered around the C19MC amplicon. Structural variations throughout the genome, including the C19MC amplicon, are highly conserved from primary tumor to relapse while other mutations show low conservation. These results suggest ETMR is an entity driven by structural variations rather than single nucleotide variants and could lead to new treatment options, specifically targeting genomic instability, to be tested in preclinical model systems of ETMR.